Surgery for endometriomas within the context of infertility treatment. (October 2019) - Dubinskaya, Ekaterina D.; Gasparov, Alexandr S.; Radzinsky, Victor E.; Barabanova, Oxana E.; Dutov, Alexandr A.
Abstract: Background: The presence of an endometrioma can often be accompanied by a clinical dilemma during the course of fertility treatment. The aim of this study was to evaluate anti-Müllerian hormone (AMH) levels and spontaneous pregnancy rate in infertility patients with endometriomas depending of initial AMH levels and cyst type. Methods: This prospective cohort study included infertility patients with unilateral endometrioma (3–5 s m in diameter) aged 25–35. A total of them underwent laparoscopic cystectomy. All patients were divided into two groups due to AMH levels and cyst type during surgery. We investigated AMH levels and spontaneous pregnancy rate in 1, 3 and 12 months after surgery. Results: The majority of patients with normal AMH level had type II endometriomas (70%) compared with low AMH level group (30%). There were no significant differences between AMH levels in all the patients with type II endometriomas after surgery. AMH level decreased significantly at 1 month in patients with normal AMH level and type I endometriomas (P = 0.018). But at 3 months the AMH level was compared with initial parameters. Women with low AMH levels before surgery and type I cysts had a significant decrease of AMH level at 1 and at 3 months after surgery. All patients with a time interval of 6 months after surgery had the best outcomes with significantly higher pregnancy rate (PR) in patients with normal AMH level and type II cysts (P = 0.036) and with AMH less than 2 ng/ml and type I cysts (P = 0.021). The group with normal AMH level and type II endometriomas had a significantly higher ongoing cumulative PR than others (59.4%). Conclusions: Our data suggest that laparoscopic surgery could affect ovarian reserve in case of initial low AMH levels and type I of endometriomas. We believe that the good surgical technique helps to increase pregnancy rate in infertility patients with endometriomas. Good prognosis group are the infertility patients with normal AMH level and type II endometriomas.